Analisis Kecurangan Laporan Keuangan: Pendekatan Fraud Pentagon Theory - Estu Ratnasari; Badingatus Solikhah (Universitas Gorontalo, 2019)
The purpose of this study aims to test the fraud pentagon theory in detecting fraudulent financial statements. It consisting of three variables from the pressure component, e.g., financial target, financial stability, and external pressure. Others, two variables from the opportunity component (effectivity monitoring and external auditor quality), one variable from the rationalization component (changes in auditor), two variables from the competency component (change of directors and board members with international experience), as well as one variable from the arrogance component (CEO duality). The research population was banking companies listed on the Indonesia Stock Exchange (IDX) in 2015-2017. Data analysis tool used is panel data regression using the program EViews 9. The results of the study show that financial stability has a negative and significant effect on fraudulent financial statements. Meanwhile, financial target, external pressure, effectivity monitoring, external auditor quality, changes in auditor, change of directors, board members with international experience, and CEO duality doesn’t effect on fraudulent financial statements. Tujuan penelitian ini adalah untuk menguji teori fraud pentagon dalam mendeteksi kecurangan laporan keuangan. Terdiri dari tiga variabel komponen tekanan yaitu target keuangan, stabilitas keuangan, dan tekanan eksternal. Selain itu, dua variabel dari komponen kesempatan (efektivitas pengawasan dan kualitas auditor eksternal), satu variabel dari komponen rasionalisasi (pergantian auditor), dua variabel dari komponen kompetensi (pergantian direksi dan pengalaman internasional anggota dewan), serta satu variabel dari komponen arogansi (CEO duality). Populasi penelitian ini adalah perusahaan perbankan yang terdaftar di Bursa Efek Indonesia (BEI) pada tahun 2015-2017. Alat analisis data yang digunakan yaitu regresi data panel dengan menggunakan program Eviews 9. Hasil penelitian menunjukkan bahwa stabilitas keuangan berpengaruh negatif dan signifikan terhadap kecurangan laporan keuangan. Sementara itu, target keuangan, tekanan eksternal, efektivitas pengawasan, kualitas auditor eksternal, pergantian auditor, pergatian direksi, pengalaman internasional anggota dewan, dan CEO duality tidak berpengaruh terhadap kecurangan laporan keuangan.